(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
Fairy tales remain one of the most malleable and enduring literary forms: as societies change, so do their narratives. In the contemporary era, classical folk and literary tales are increasingly being modernized and re-written. These adaptations reflect new cultural norms, address current social issues, and reinterpret traditional archetypes. At the same time, the way fairy tales are understood (“interpretation”) differs in English-speaking contexts versus Uzbek contexts, shaped by their respective literary traditions and cultural values. Thematic Renewal: Modern retellings often engage with themes that resonate today — such as gender equality, identity, social justice, and environmental concerns.